Formation of economic competence of the head of the educational organization in terms of professional development - M.G, Sergeeva (2019)
Today, the professional activity of the head of an educational organization is inseparable from the economic context. Economic activity of the head of the educational organization is to provide the organization with the necessary resources for its effective functioning and demand for educational services. In the context of modernization of the Russian education system, the key factor is the compliance of professional competence of heads of educational institutions with the needs of the time.   Professional competence of the head of the educational institution is determined by a set of competencies, which are characterized by the ability to use theories and concepts, knowledge in various fields of activity, the gained experience; the ability to positive intellectual, volitional self-development, interaction with other people, groups, team; the presence of motives to respect the rights and interests of the individual in the course of management; personal attitude to activity. In the structure of economic competence of the head of the educational institution knowledge, activity, motivational and personal components are identified that provide professional and personal improvement and self-development of the head, the formation of his abilities, characterized by three types of competencies: marketing, business and economic and legal. To determine the level of economic competence formation in the educational process of the professional development system four formation levels (insufficient, basic, advanced and leadership) of economic competence of the head are identified, where each previous determines the subsequent one and is included in its composition. The study is aimed at solving one of the important problems of modern postgraduate education – ensuring the effectiveness of the process of professional development of heads of educational institutions. The professional development system is able to solve the problem of formation of economic competence of heads of educational institutions quickly.